2008
DOI: 10.1523/jneurosci.3512-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18-Mediated Microglia/Astrocyte Interaction in the Spinal Cord Enhances Neuropathic Pain Processing after Nerve Injury

Abstract: Interleukin (IL)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
206
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(214 citation statements)
references
References 60 publications
8
206
0
Order By: Relevance
“…Notably, we found increases in the expression of both IL-18 in microglia on day 3 and IL-18Rs on day 7 after TSS. This is consistent with previous reports that microglial IL-18 expression significantly increases on day 3 after excitotoxic damage and IL-18-mediated interaction between spinal microglia and astrocytes enhances neuropathic pain [21,26] . Therefore, it is conceivable that the [49,50] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Notably, we found increases in the expression of both IL-18 in microglia on day 3 and IL-18Rs on day 7 after TSS. This is consistent with previous reports that microglial IL-18 expression significantly increases on day 3 after excitotoxic damage and IL-18-mediated interaction between spinal microglia and astrocytes enhances neuropathic pain [21,26] . Therefore, it is conceivable that the [49,50] .…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that IL-18 mediates the interaction between microglia and astrocytes via binding to IL18Rs [21,26] , so the effects of minocycline on IL-18R expres- following TSS (Fig. 4A).…”
mentioning
confidence: 91%
“…34 Inhibition of IL-18 reduces nuclear factor-κB phosphorylation in spinal astrocytes and suppresses the induction of astroglial markers. 35 TNF-α can induce spinal cord motoneuron death 36 and exacerbate cell death after SCI. 37 Topical application of TNF-α antiserum can alleviate edema, microvascular permeability and cell injury in rat SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Although the answers to these questions are unknown, the different time courses suggest a hierarchical activation of glial cells. In this context, Miyoshi et al (2008) showed that the TH-1-stimulating cytokine IL-18 is an important communicator between activation of microglia and astrocytes in the spinal cord during neuropathic pain, and this cytokine might mediate sequential activation.…”
mentioning
confidence: 99%
“…Therefore, one simple experiment that (Miyoshi et al, 2008). IL-18 seems to mediate the interaction between activated microglia and astrocytes.…”
mentioning
confidence: 99%